Determinan kecelakaan kerja pada peserta BPJS ketenagakerjaan cabang Palembang - Ibrahim Syahputra; Novrikasari Novrikasari; Yunita Windusari (Holistik Jurnal Kesehatan, 2022)
Background: Causing injury or pain (depending on the severity), even death. The ILO estimates that 2.34 million people died due to 86 percent due to work-related diseases and 14 percent due to work-related accidents. Data from the Employees' Social Security System in Palembang Region, it is known that there are 10,334 work accident insurance claims in 2021.Purpose: To analyze the most dominant factor causing the number of work accidents among Employees' Social Security System members in PalembangMethod: An analytic descriptive study with a cross-sectional approach. The sample in this study was all Employees of Social Security System members in Palembang Branch who experienced work accidents n=1856. This study uses secondary data obtained from reporting Employees of the Social Security System in 2021. Data analysis includes univariate analysis, bivariate analysis using the chi-square statistical test, and multivariate analysis using the logistic regression statistical test.Results: Showed that 3.6 percent of workers had serious work accidents, 84.4 percent of workers had moderate work accidents, and 12 percent of workers had mild work accidents. There is a significant relationship between age (p-value=0.007; OR=2.007), type of participation (p-value=0.025; OR=2.936), work environment risk (p-value=0.0001), work location (p-value=0.046; OR=1.705), and unsafe conditions (p-value=0.044; OR=1.808) with the level of work accidents. The most dominant factor affecting the level of work accidents is unsafe conditions.Conclusion: There is a correlation between age, work environment risks, accident locations, and unsafe conditions with work accidents, while the length of work is confounding. The most dominant factor in the accident rate is unsafe conditions.Keywords: Work accidents; Employees' social security system; Work environmentPendahuluan: Menyebabkan cidera atau kesakitan (tergantung dari keparahannya), bahkan kematian. ILO memperkirakan sebanyak 2,34 juta orang meninggal dunia diakibatkan oleh 86 persen karena penyakit akibat kerja dan 14 persen kecelakaan akibat kerja. Data BPJS Ketenagakerjaan Wilayah Palembang, diketahui bahwa klaim jaminan kecelakaan kerja sebanyak 10.334 Kasus pada tahun 2021.Tujuan: Menganalisa faktor paling dominan yang menyebabkan terjadinya tingkat kecelakaan kerja pada peserta BPJS Ketenagakerjaan Cabang Palembang.Metode: Penelitian deskriptif analitik dengan pendekatan Cross Sectional. Sampel pada penelitian ini adalah seluruh tenaga kerja yang dilaporkan di Kantor BPJS Ketenagakerjaan Cabang Palembang yang mengalami kecelakaan kerja sebanyak 1856 pekerja. Penelitian ini menggunakan data sekunder yang diperoleh dari pelaporan pembayaran klaim kecelakaan kerja di Tahun 2021. Analisis data meliputi analisis univariat, bivariat menggunakan uji statistik chi square, dan multivariat menggunakan uji statistik regresi logisticHasil: Menunjukkan bahwa sebesar 3,6 persen pekerja mengalami kecelakaan kerja berat berat, 84,4% pekerja mengalami kecelakaan kerja sedang, dan 12 persen pekerja mengalami kecelakaan kerja ringan. Ada hubungan yang signifikan antara usia (p-value=0,007; OR=2,007), jenis kesertaan (p-value=0,025;OR=2,936), resiko lingkungan kerja (p-value=0,0001), lokasi kerja (p-value=0,046;OR=1,705), dan kondisi tidak aman (p-value=0,044;OR=1,808) dengan tingkat kecelakaan kerja. Faktor paling dominan yang mempengaruhi tingkat kecelakaan kerja adalah kondisi tidak aman.Simpulan: Adanya korelasi antara usia, resiko lingkungan kerja, lokasi kecelakaan, dan kondisi tidak aman dengan kecelakaan kerja, sedangkan lama kerja merupakan confounding. Faktor paling dominan terhadap tingkat kecelakaan adalah kondisi tidak aman.